Sabaic and Aramaic — a common origin? - Kottsieper, Ingo; Stein, Peter (Proceedings of the Seminar for Arabian Studies, 2014)
The origin of civilization in pre-Islamic South Arabia is closely connected with the linguistic affiliation of the Ancient South Arabian languages. That these languages have some particularities in common with the North-west Semitic language realm has been known for a long time. Recent investigations, however, allow us to confine these isoglosses in particular to the Aramaic and the Sabaic branches of both language groups, suggesting a fairly close linguistic relationship between these two languages. Since these isoglosses are definitely not shared by other South Arabian languages such as Minaic and Hadramitic, the traditional picture of a linguistic continuity of the so-called Ancient South Arabian language group gets broken up. Consequently, the question of a cultural transfer across the Arabian Peninsula arises anew. On the other hand, the assumption of Aramaic as a member of an alleged Northwest Semitic language group should also be questioned on the basis of these isoglosses. The linguistic evidence and its historical implications are examined from an Aramaist’s and a Sabaist’s perspective.